Serum B-cell maturation antigen (BCMA) reduces binding of anti-BCMA antibody to multiple myeloma cells. (June 2019) - Chen, Haiming; Li, Mingjie; Xu, Ning; Ng, Nicole; Sanchez, Eric; Soof, Camilia M.; Patil, Saurabh; Udd, Kyle; Bujarski, Sean; Cao, Jasmin; Hekmati, Tara; Ghermezi, Matthew; et al.
Highlights: Patients with BCMA ≥156 ng/mL have decreased anti-BCMA binding to MM tumor cells. Circulating BCMA levels in the majority of RRMM patients are elevated. Levels of BCMA in most MM patients interfere with anti-BCMA binding to tumor cells. Circulating BCMA may interfere with BCMA-targeted immune-based therapies. Abstract: B-cell maturation antigen (BCMA), a tumor necrosis factor receptor (TNFR) family member, is selectively expressed on terminally differentiated B-lymphocytes including multiple myeloma (MM) tumor cells. We sought to determine whether circulating (c)BCMA in MM serum interferes with antiBCMA antibody binding to MM cells. An enzyme-linked immunosorbent assay (ELISA) was used to determine serum (s) BCMA levels among 379 samples from patients with relapsed/refractory MM (RRMM). Furthermore, flow cytometric and immunofluorescent studies were used to examine if concentrations of BCMA in patients' serum were high enough to interfere with the binding of anti-BCMA antibody to MM tumor cells. We have shown that BCMA is elevated in the serum from MM patients and that the median concentration of sBCMA from RRMM patients was 176 ng/mL (n = 379). Additionally, there was a consistent decrease in the binding of anti-BCMA antibody to MM tumor cells with sBCMA level ≥156 ng/mL. Together, these results demonstrate that circulating BCMA levels in most RRMM patients are high enough to interfere with anti-BCMA antibody binding to MM tumor cells and may interfere with BCMA-targeted immune-based therapies.